Flood vulnerability and flood risk of flood-hit households in the east coast region of peninsular Malaysia - Mohamad Syafiqi, Hashim (2019)
Faced with increasing flood events and the associated losses, a systematic record towards assessing the multiple aspects of flood vulnerability; physical, social, economic and environmental is crucial for a developing country such as Malaysia. Thus, the general objective of this study is to develop a household-based flood vulnerability index of Malaysia (MyFVI) as a baseline estimator of vulnerability and to analyse the fundamental link between flood vulnerability and flood risk among the flood-hit households. Following the 2014’s major flood, this study adopts the FVI methodology in assessing the flood vulnerability levels among 380 affected households in six districts; Kota Bharu, Kuala Krai, Kuala Terengganu, Kemaman, Kuantan and Temerloh within the East Coast region of Peninsular Malaysia. Specifically, it aims to measure the exposure, susceptibility and resilience elements, estimate the flood vulnerability levels, compare the spatial (i.e. district and state) differences in economic vulnerability and evaluate the effect of flood vulnerability on flood risk among the households. The MyFVI development integrates the use of primary and secondary data. Multiple regression analysis is employed to analyse the relationships between flood vulnerability, economic vulnerability and flood risk. Among others, this study unfolds that the district of Kuala Krai and the state of Terengganu as the most vulnerable district and state with the FVI average values of 0.631 and 0.568, respectively. Also, this study reveals that proximity to river, businesses, flood insurance holders and economic recovery are key economic vulnerability indicators that influence changes in flood risk among the households. Therefore, policy makers are recommended to explore possible ways of optimizing the flood recovery process from pre-disaster community policies such as code adoption policies, early recovery decisions and uninterrupted lifeline services via vertical and organizational integrations among households, communities, businesses, donor agencies, infrastructural providers and local governments.